Carbon emissions analysis for tuna transportation from Samudera Kutaraja fishing port - Umiralaska Salsabila; Budhi Hascaryo Iskandar; Vita Rumanti Kurniawati; Muhammad Fedi Alfiadi Sondita (Depik, 2024)
The tuna fishing industry significantly contributes to greenhouse gas (GHG) emissions primarily through fuel oil usage. This study investigates the environmental impact of tuna transportation, focusing on emissions from fishing vessels and vehicles. Carbon footprint calculations for fishing vessels utilize the IPCC, 2006 formula as referenced in KLH, 2012. Smaller purse seiners (10-20 GT) emit 2.88 kg CO2per trip per kilogram of tuna, while those (20-30 GT) in PPS Kutaraja emit 3.58 kg CO2. Larger purse seiners exhibit higher emission rates: 7.3 kg CO2 (20-30 GT), 9.9 kg CO2 (30-40 GT), 8.6 kg CO2 (40-50 GT), and 8.4 kg CO2 (50-60 GT) per trip per kilogram of tuna. Vehicle emissions for tuna transport vary, with the Honda Blade FI 125 emitting 0.00625 kg CO2, Supra X 125 emitting 0.00450 kg CO2, Viar Tiga Roda emitting 0.00458 kg CO2, Revo Fit emitting 0.0007 kg CO2, Jupiter emitting 0.00063 kg CO2, and Vega ZR Yamaha emitting 0.0006 kg CO2 per kilogram of tuna.Keywords:Carbon FootprintEmissionFsihing VesselsGreen TransportationsSupply ChainFishing Activties